Strategi BPOM dalam upaya mengatasi Pemberantasan dan Penyalahgunaan obat Ilegal melalui Gerakan “Waspada Obat Ilegal” - siti qonaah qonaah; Heri Afianto (Jurnal Komunikasi, 2020)
The distribution of illegal drugs is a serious problem that not only occurs in Indonesia, but globally. In Indonesia, the Food and Drug Supervisory Agency (BPOM) noted the growth of illegal drug circulation in the last few years was quite high. The "Illegal Drug Alert" Movement is an effort implemented by BPOM in overcoming the eradication and abuse of illegal drugs, the strategy being implemented includes prevention, detection / supervision and response / action. This research is to find out the BPOM Strategy in an effort to overcome the Eradication and Abuse of Illegal Drugs through the "Illegal Drug Alert" Movement. In this study, researchers used a qualitative approach and case studies. As a research method that describes the vigilance of illegal drugs can be useful in overcoming the eradication and abuse of illegal drugs